2002
DOI: 10.1063/1.1471570
|View full text |Cite
|
Sign up to set email alerts
|

Spin-coherent transport in ferromagnetically contacted carbon nanotubes

Abstract: The spin-coherent quantum transport through multiwall carbon nanotubes contacted by ferromagnetic Co pads is investigated experimentally. At 4.2 K, the devices show a remarkable increase of the magnetoresistance (MR) ratio with decreasing junction bias, reaching a maximum MR ratio of 30% at a junction bias current of 1 nA. The experimental results suggest the transport to be dominated by spin-dependent tunneling processes at the Co/nanotube interfaces and governed by the local magnetization. We also observe an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
134
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(140 citation statements)
references
References 19 publications
6
134
0
Order By: Relevance
“…The results depend very strongly on ferromagneticelectrode/CNT interfaces, yielding the net GMR effect of the order of 10 -40%. It should be stressed however that also inverse GMR has been reported of roughly similar magnitude but with negative sign [15,17]. A very surprising data concerning Fe-contacted SWCNT were reported in [16], where a measured GMR effect approached 100%, i.e.…”
Section: Gmr In Carbon Nanotubesmentioning
confidence: 90%
See 1 more Smart Citation
“…The results depend very strongly on ferromagneticelectrode/CNT interfaces, yielding the net GMR effect of the order of 10 -40%. It should be stressed however that also inverse GMR has been reported of roughly similar magnitude but with negative sign [15,17]. A very surprising data concerning Fe-contacted SWCNT were reported in [16], where a measured GMR effect approached 100%, i.e.…”
Section: Gmr In Carbon Nanotubesmentioning
confidence: 90%
“…Bearing in mind, that nowadays CNT lengths used in electric current measurements, are quite often as short as 200-250 nm, it means that practically electrons travel through nanotubes in a spin-coherent way (no spin flips). Experimental papers concern mostly MWCNTs electrically contacted by cobalt [14,15], but there are also reports on iron [16] and permalloy [17] contacted multi-walled and single wall carbon tubes. The results depend very strongly on ferromagneticelectrode/CNT interfaces, yielding the net GMR effect of the order of 10 -40%.…”
Section: Gmr In Carbon Nanotubesmentioning
confidence: 99%
“…To illustrate the enormous scientific and technological progress that has been made since carbon nanotubes were discovered it is worth to mention new concepts such as: the room temperature single electron transistor, 1 the ballistic carbon nanotube field-effect transistor 2 or the non-volatile random access memory for molecular computing. 3 Recently several both experimental 4,5,6 and theoretical 7,8,9 papers have been published on spin-dependent electrical transport in ferromagnetically contacted carbon nanotubes in an attempt to test their ability to operate as spintronic devices. It has been found that carbon nanotubes -though intrinsically nonmagnetic-reveal quite a considerable GMR effect.…”
Section: Introductionmentioning
confidence: 99%
“…However, additional effects, such as the anomalous magnetoresistance, can contribute to the observed signal in spin-valves [3,4,5,6]. It seems clear, that despite a number of large responses seen in CNT-based devices [1,7,8,9], one needs to go beyond two terminal structures by realizing multi-terminal devices where non-local measurements are feasible [10]. The non-local measurement in spin-valve devices has been pioneered by Johnson and Silsbee [11] in metallic spin-valves and was further applied to various other systems [12,13,14].…”
mentioning
confidence: 99%